Isolation and Preliminary Characterisation of Active B-Chain of Recombinant Tissue-Type Plasminogen Activator - Dodd, I; Fears, R; Robinson, J H (Thrombosis and Haemostasis, 1986)
Purified 2-chain recombinant tissue-type plasminogen activator (t-PA) was reduced under mild conditions - 10 mM dithiothreitol/ 5° C/1.5 h - and the two chains were separated by chromatography on lysine Sepharose. The t-PA B chain was fully active as determined by its activity towards the chromogenic substrate S-2288 (H-D-ile-pro-arg p-nitroanilide). Analysis by sodium dodecyl sulphate polyacrylamide gel electrophoresis under reducing or non-reducing conditions revealed a single polypeptide at Mr = 35,000 or 29,000 respectively. In addition, under non-reducing conditions a fibrinolytic band at apparent Mr = 29,000 was present after fibrin zymography. The N-terminal sequence was confirmed as ile-lys-gly. The t-PA B chain had a specific amidolytic activity, using S-2288, of 170,000 to 210,000 SU/mg protein. (This compares to a specific activity of the native 2-chain t-PA of 170,000 SU/mg). It resembles urokinase-type plasminogen activator in its inability to be stimulated by fibrin and its dose response on human fibrin plates. However, t-PA B-chain was stimulated to almost the same extent as t-PA by poly-D-lysine. The isoelectric points, at pH 5.6 and 5.7, fall outside the range generally quoted for t-PA preparations (pH 7.8-8.8).
Keywords: Tissue-type plasminogen activator; Fibrinolysis; Urokinase-type plasminogen activator